Rediscovery, taxonomic status, and phylogenetic relationships of two rare and endemic snakes (Serpentes: Psammophiinae) from the southwestern Angolan plateau - Branch, William R.; Baptista, Ninda; Keates, Chad; Edwards, Shelley (Zootaxa, 2019)
Two rare and endemic psammophines (Serpentes: Psammophiinae) occur in Angola. The taxonomic status of Psammophylax rhombeatus ocellatus Bocage, 1873 and Psammophis ansorgii Boulenger, 1905 have long remained problematic, with both having varied past and present taxonomic assignments, and whose distributions may therefore present zoogeographic anomalies. Little was known of their biology, habitat associations, or phylogenetic relationships. New material was collected during biodiversity surveys of the Humpata Plateau, near Lubango, Angola. It allowed fuller descriptions of scalation and live coloration for both species, and resolution of their taxonomic status. Genetic analysis confirms that both are distinct at the specific level. In addition, within Psammophis, Jalla’s Sand Snake (Psammophis jallae Peracca, 1896), of which P. rohani Angel, 1925, remains a synonym, is sister to P. ansorgii, and Boulenger’s comment on similarities with P. crucifer are not supported. The status of an unusual skaapsteker from Calueque, Cunene Province, Angola, is discussed and its assignment to Ps. ocellatus is provisional and requires additional material for taxonomic resolution. The new P. ansorgii records from Tundavala represent a range (+400 km southwest) and altitude (1800 m to 2286 m a.s.l) extension from the previous only known precise locality of Bela Vista (= Catchiungo), Huambo Province, whilst that for Ps. ocellatus doubles the known altitude from 1108 m to 2286 m a.s.l and extends the range about 122 km to the northwest from historical material from the plateau of Huíla and Cunene provinces.